2004
DOI: 10.1177/0886260504263875
|View full text |Cite
|
Sign up to set email alerts
|

Observations From Practice

Abstract: This article explores the authors' practice observations of female domestic violence survivors' journey from first agency contact to active participation in a support group process. The authors have witnessed female victims of domestic violence challenging the social isolation imposed by their dominant partners as they search for meaning in their lives. As practitioners, they have observed women building trustful relationships and establishing supportive networks during the group process. In this article, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…As a result, participants were able to relax and appreciate the full benefit of the crafting experience, including the recognition that crafting can be a non-pharmacological intervention to soothe the self and a useful self-care tool in the management of anxiety and anger. Group members also benefited from the enhanced socialization and communica-tion processes inherent in the group format identified in similar studies [10] [31].…”
Section: Discussionmentioning
confidence: 86%
“…As a result, participants were able to relax and appreciate the full benefit of the crafting experience, including the recognition that crafting can be a non-pharmacological intervention to soothe the self and a useful self-care tool in the management of anxiety and anger. Group members also benefited from the enhanced socialization and communica-tion processes inherent in the group format identified in similar studies [10] [31].…”
Section: Discussionmentioning
confidence: 86%
“…For example, those who seek support may encounter waiting lists for specialist therapy, which have the effect of exacerbating their distress (Sanderson, 2012). Other barriers to recovery may include the cognitive and interpersonal avoidance strategies that survivors of sexual violence may develop in order to cope with the after-effects of trauma (Burgess & Holmstom, 1979) and a lack of social support (Larance & Porter, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Police may take a passive stance toward cases of domestic violence, feeling that men are rightfully in a dominant position within the family (Websdale, 1995). On the other hand, women, viewing their family life as a private matter, may be too embarrassed and ashamed to voice their abusive experiences (Larance and Porter, 2004).…”
mentioning
confidence: 99%
“…TSH facilities may also combat social isolation by providing support groups and a broad support system where women can learn how to develop healthy friendships and social networks. Larance and Porter (2004) found that a support group for survivors of IPV provided women with the opportunity to divulge sensitive, personal experiences with one another. They also found that the conversations extended beyond the confines of the support group and developed into friendships.…”
mentioning
confidence: 99%
See 1 more Smart Citation